-2(x + 3) = -2(x + 1) - 4
-2x - 6 = -2x - 2 - 4 <em>distributed -2 on the left and on the right</em>
-2x - 6 = -2x - 6
<u>+2x </u> <u>+2x </u>
-6 = -6
TRUE
Since this is a true statement, there are infinite solutions (aka All Real Numbers)
Answer: C
Answer:
12
Step-by-step explanation:
12
Answer:
dy/dx = (cos y + y sin x) / (cos x + x sin y)
Step-by-step explanation:
y cos x = x cos y
y (-sin x) + dy/dx cos x = x (-sin y dy/dx) + cos y
-y sin x + dy/dx cos x = -x sin y dy/dx + cos y
dy/dx (cos x + x sin y) = cos y + y sin x
dy/dx = (cos y + y sin x) / (cos x + x sin y)
Answer:
D
Step-by-step explanation:
(7^-2)*(7^6)=7^-2+6
......since the base 7 is the same, when u multiply them, you should add the exponents and keep 7 as it is. That will be 7^4, which in equivalent to ans D(7^2)^2.
An expression is just like an equation but without the equal sign.